Penerapan Model Unified Theory of Acceptance and Use Of Technology Untuk Mengetahui Faktor yang Mempengaruhi Perilaku Penggunaan QRIS - Permatasari, Rizky Puput; Sari, Shinta Permata (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
The advancement of payment technology has shifted the role of cash to non-cash systems. Generation Z plays a significant role in the adoption of this technology. One of the innovations introduced by Bank Indonesia is the Quick Response Code Indonesian Standard (QRIS), launched on August 17, 2019, to support digital payments through server-based e-money applications, e-wallets, or mobile banking. This study aims to analyze the factors influencing QRIS usage behavior among Generation Z based on the Unified Theory of Acceptance and Use of Technology (UTAUT). The study employs a quantitative method involving 275 respondents collected through an online questionnaire. Data are analyzed using SmartPLS. The results show that performance expectancy, facilitating conditions, and social influence have a positive influence on QRIS usage behavior. In contrast, effort expectancy does not have an influence. These findings are expected to support strategies for increasing QRIS adoption among Generation Z.